Attacking anxiety & depression - Bassett, Lucinda; Midwest Center for Stress and Anxiety (Oak Harbor, OH : Midwest Center for Stress and Anxiety, 2002)
A self-help, self-awareness audio study program for depression, anxiety and agoraphobia, divided into 15 sessions. In the motivational DVD's, Lucinda Bassett talks about anxiety, her life, and personal experiences.
Compact discs: Introduction: Relaxation ; I will be there for you -- Sessions 1-4: Session 1, Anxiety and depression (symptoms, causes & common fears) ; Session 2, Six steps designed to put an end to panic attacks ; Session 3, Self-talk (the key to healthy self esteem) ; Session 4, Expectations (how to expect less and get more) -- Sessions 5-8: Session 5, Eat and exercise to minimize anxiety and depression ; Session 6, Stop being angry & control your mood swings ; Session 7, Assertive behavior (speak confidently and gain respect) ; Session 8, Put an end to 'what if' thinking -- Sessions 9-12: Session 9, Get off the guilt and worry treadmill ; Session 10, How to address obsessive, scary thoughts ; Session 11, Anxiety and depression (a candid dialogue about medication and alcohol) ; Session 12, The courage to change -- Sessions 13-15: Session 13, Time management (12 steps toward a balanced life) ; Session 14, How to keep stress from becoming anxiety) ; Session 15. Getting beyond a growth spurt ; Bonus CD, Feel better fast!
Title from disc labels.
Presented by Lucinda Bassett.
Guidebook accompanies introduction and each group of sessions.
Sound discs are compact discs.
Keywords: Depression, Mental; Anxiety; Stress management